Assessing Supraspinatus Tendon Elasticity at Different Locations and Loading Conditions Using Ultrasound Shear-Wave Elastography in Young Healthy Population - Arash Azhideh; Peyman Mirghaderi; Sara Haseli; William D. Lack; Karen C. Takatani; Liisa C. Hammer; Kevin F. Malik; Hannah Tifft; Kyle Griffith; Majid Chalian (Diagnostics)
Objective: This prospective study aims to investigate the feasibility of Shear-Wave Elastography (SWE) for assessing the mechanical properties of the normal supraspinatus tendon and describing the elastographic features of the supraspinatus tendon under different loading conditions and positions. Methods: Twenty healthy volunteers (10 males and 10 females, aged 18–25 years) were examined by SWE using an 18-4 MHz linear array transducer. The elasticity of the supraspinatus tendon of the dominant hand was measured at three distinct locations: the insertion, middle, and myotendinous junction of the tendon. These measurements were taken under various conditions, including non-loading and the application of 5, 10, and 20 lb forces at five different positions. Results: The average elasticity was 69.2 ± 26.5 kilopascals across all positions and forces, with the middle part of the tendon exhibiting the highest elasticity (72.6 ± 6.2 kPa). An ascending trend in elasticity was observed by increasing the applied load, and the highest elasticity was observed with a 20 lb load. Determining the normal elasticity of the tendon is an important clinical implication, as understanding what is normal is essential for identifying pathological conditions. Conclusions: SWE is a feasible and promising technology for the collection of data on how the supraspinatus tendon behaves under loading conditions. There is a need for further study to better understand tendon response to activity and resultant injuries.